Does instruction through mother tongue impede students’ English proficiency? public skepticism on the instructional language policy in the state of Amhara - Melaku Gebremeske (Bahir Dar Journal of Education)
This study examined whether learning in the mother tongue affects students’ English proficiency in the State of Amhara. It also explores experiences across the world to look for possible means of equipping students with the required competences of English. The study depended on a review of literature and documentary examination. It has employed the content analysis method of the qualitative approach. Findings revealed that instruction through mother tongue per se does not impede the acquisition of English proficiency nor does the use of English as medium of instruction necessarily improve pupils’ English proficiency. Rather, lack of carrying out valid instructional language planning, government reluctance to consult necessary stakeholders during policy formulation and poor implementation procedures have resulted in lack of realizing the intended goals of the instructional language policy. Apart from lack of resource supply the defects in its formulation procedure have lingering effects on the realization of instructional language policy. In general, although many scholars of the field have labeled the current policy as one of the best instructional language policies formulated in Ethiopia so far, the irregularities and inconsistencies in its practice hindered to meet the intentions advocated from the outset. Consequently, the implementation of instruction through the mother tongue, like similar interventions by previous governments, has been a matter of political expediency rather than a well thought out and planned reform. Hence, since the future is today, employing a contextually sound instructional language policy alleviates the challenges pupils face in their English proficiency and ultimately helps them compete in the prevailing globalizing socio-economic world.